Pengaruh Nilai Intrinsik, Lingkungan Kerja, dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Akuntansi untuk Berkarir Sebagai Akuntan Publik - Selvia Selvia; Risca Azmiana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The existence of public accountants helps reduce information asymmetry between management as the manager and company owners as the principal, as well as between the company and external parties. This research evaluates the effect of intrinsic value, work environment, job market considerations on accounting students’ interest in pursuing a career as a public accountant in Batam city. The study applies a quantitative method. The population includes 290 accounting students in Batam city. The sample size follows the Slovin calculation, producing 290 respondents. Data collection applies questionnaires. Validity testing, reliability testing conducted. Data processing applies multiple linear regression. The findings indicate intrinsic value gives a positive, significant impact on students’ career interest as a public accountant. Work environment gives a positive, significant impact on students’ career interest as a public accountant. Job market considerations give a positive, significant impact on students’ career interest as a public accountant. Simultaneous testing indicates all independent variables affect the dependent variable.